Tunable multiresponsive methacrylic acid based inverse opal hydrogels prepared by controlling the synthesis conditions - Wang, Jianying (Langmuir : the ACS journal of surfaces and colloids, 2009)
Methacrylic acid based inverse opal hydrogels (MIOHs) have been prepared by controlling the synthesis conditions, including cross-linker content, solvent content, and water content in solvent mixtures to explore the effect of the synthesis conditions (especially solvent content and mixture) on the response performance. Various response events (pH, solvent, ionic strength, 1,4-phenylenediamine dihydrochloride (PDA) response) have been investigated. For pH, solvent response, the same response behaviors have been observed: both the increased solvent (only ethanol) content and the enhanced water content in solvent will lead to the reduced response level of MIOHs compared to that of the increased cross-linker content. However, two different kinds of response behaviors for ionic strength response have been found by adjusting the synthesis conditions. The kinetics of pH response shows characteristics of a diffusion-limited process, and the equilibrium response time is about 20 min, which cannot be reduced by changing the synthesis conditions. The PDA response of MIOHs shows a PDA concentration dependence: with the increase of PDA concentration, the response level increases and the response time decreases